Reshaping the future : phenomenon of gig workers and knowledge-economy - Moghavvemi, Sedigheh; Teng, Lee Su; Mahmoud, Huda (Emerald Publishing Limited, 2023)
The labour economy is being transformed by new technology, as employers embrace new practices that utilise flexible work contracts and a whole new generation of tech-savvy employees. Leaders and decision-makers, managers and aspiring professionals, and a whole generation of students soon to join the workforce, will find Reshaping the Future: Phenomenon of Gig Workers and Knowledge-Economy invaluable. Unique insight is given into the changing business environment and the laws that are being created to regulate it. Those that adopt successful strategies, as set out by Moghavvemi, Teng, and Mahmoud will have the competitive edge needed to survive these changes, and thrive, well into the mid-twenty-first century.